ANALYSIS OF STOCK MARKET DYNAMICS - BURTNYAK, Ivan; RUSYN, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the application of information technologies to the analysis of the stock market, namely to the study of the dynamics of the Ukrainian currency exchange rate, which will allow us to draw a conclusion about the market as a whole. Exploratory data analysis was used to review and analyze financial data. It is an approach to summarizing, visualizing, and gaining insight into the important characteristics of a data set. When analyzing and predicting the dynamics of complex financial systems, one cannot do without such a powerful tool as the Python programming language and neural network technologies. Neural networks find new successful applications in the practice of management and decision-making, including in the financial and trade spheres, i.e. wherever it is necessary to find a certain hidden regularity and make a forecast of stock market tools aimed at achieving macroeconomic stabilization and dynamic development of the financial market. Forecasting of the dynamics of stock market instruments is carried out, which allows for analysis and precautionary conclusions and proposals to minimize risks related to the pricing of derivatives that arise on the stock market. Neural networks are used for forecasting the exchange rate, which allows to minimize speculative changes in pricing, to analyze the progress of processes on the stock market and to take specific steps to improve the situation regarding the optimization of financial strategies. As a result of the analysis, it can be noted that information technologies are widely used in the financial sphere of activity. The effectiveness of the use of information technologies for data analysis and the ability of neural networks to one of the most sought-after tasks of financial activity - forecasting the future value of various instruments - have been proven. It can be argued that the best result is given by the combination of information technologies with expert systems, it allows to calculate the value of derivatives prices with great accuracy and to monitor changes in the speed of financial flows. The used technique allows to increase the accuracy of the forecast and to make informed management strategic decisions by the participants of the stock market.
Keywords: Stock market; financial market; currency market; financial systems; research data analysis; neural network